The Role and Important of Internet of Things in Building Sustainable City - Nahla Alwan; Muna AL-Nuaimi (Engineering and Technology Journal, 2018)
Every year many people migrate from country to city to live there. This will load a big pressure on the whole living in the city, Baghdad city also suffer from this problem in addition to other found problems like energy consumption , waste accumulate , Traffic congestion, noise, environmental pollution. To offer a good sustainable future living to population without any damage to environment and to solve many problems , one can use internet of things which is the connection network of the things especially with high spread of networks now which Internet of things based on it .the purpose of this research is to explain internet of things (IoT) and its role in solving many problems in the city , by using of the data collect by internet of things and to respond in real time to know problems and to enable planning and building city in a valuable sustainable way . As well as to explain the concept and models of smart city and its relationship to the sustainable city and Internets of things. In addition, to demonstrate in a simplified way the possibility of using the Internet of things to solve the problems in the Baghdad city and to raise the standard of life of its inhabitant is in a sustainable smart way. Taking this in the strategic planning of Baghdad city.